The Symbolism of the Sembeq Senggeteng Ritual in Preventing Early Marriage in Wanasaba Daya - Dea Mustika (Tabéq Care Center and UIN Mataram, 2025)
Early marriage (merarik kodeq) remains a prevalent phenomenon in Wanasaba Daya Village, Wanasaba District, East Lombok. One of the efforts made by the Sasak community to prevent early marriage is through the traditional Sembeq Senggeteng ritual. This ritual, which consists of incantations or mantras passed down through generations, is believed to possess symbolic and spiritual power to protect children, especially teenagers, from focusing on education and avoiding romantic relationships at a young age. This study aims to uncover the symbolic meaning embedded in the Sembeq Senggeteng ritual and its implementation process in preventing early marriage. The research approach employed is a descriptive qualitative one, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data were analysed using George Herbert Mead's symbolic interactionism theory, which emphasises that symbolic meaning is formed through social interaction. The results of the study indicate that the Sembeq Senggeteng ritual is performed by traditional leaders or elders, who recite prayers or mantras believed to bind the hearts of children. This ritual process reflects social symbols rich in moral values and hopes, serving as a means of symbolic communication between parents and children. The ritual also reflects collective social values upheld by the community as a form of social control over adolescent behaviour. In conclusion, the Sembeq Senggeteng ritual holds a strong symbolic meaning, instilling moral messages and promoting social control, particularly in preventing early marriage. However, the challenges of the times and changes in the mindset of the younger generation are beginning to affect the effectiveness of this tradition.